ANALISIS DUKUNGAN KELUARGA DENGAN KEPATUHAN TERAPI ANTI RETRO VIRAL PADA WANITA HIV/AIDS - LELLY APRILIA VIDAYATI (NHM PRESS, 2020)
HIV (Human Immunodeficiency Virus) the virus that causes AIDS by attacking the CD4 cells, The way to prevent the decrease of CD4 lymphocytes by Anti Retro Viral therapy. The purpose of this researchis to analyze the relationship of family support with anti retro viral therapy adherence of women with HIV / AIDS at Yayasan Mahameru Surabaya. This research used cross sectional analytic, with independent variable of family support and the dependent variable of antiretroviral therapy adherence in women with HIV. The total population of women with HIV / AIDS is 32 women with the sample is 30 women. The sampling technique using Simple Random Sampling. The instrument used is Questionnaire. The results were analyzed using univariate and bivariate. Statistical test using Spearman rank with α (0,05). The results showed that almost all HIV / AIDS women who had good family support were adherent to viral anti retro therapy as many as 18 women (78.3%). And for enough family support most HIV / AIDS women do not adhere to viral anti retro therapy as many as 5 women (71.4%). Based on statistical test of Spearman's rho (rs) probability value (ρ) indicates that the value of ρ <from level of significant 5% (0,014 <0,05). It can be concluded that there is a relation of family support with viral anti retro viral adherence in HIV / AIDS women at Yayasan Mahameru Surabaya Year 2018. The results of this research are expected to be used as an additional discourse for further research in reviewing and developing several other factors that are associated or that affect the adherence of anti retro viral therapy.